GENOME OF MICROBULBIFER sp. CCB-MM1 - CCB, Pusat Biologi Kimia (Pusat Biologi Kimia, 2017)
Moh Tsu Horng , a MSc student alongside Dr. Lau Nyok Sean, Dr. Go Furusawa and Prof. Dr. Amirul Al-Ashraf Abdullah have published a research article titled “Complete genome sequence of Microbulbifer sp. CCB-MM1, a halophile isolated from Matang Mangrove Forest, Malaysia” in Standards in Genomic Sciences.